Achieving ferromagnetic insulating properties in La0.9Ba0.1MnO3 thin films through nanoengineering. Issue 16 (20th April 2020) - Yun, Chao; Choi, Eun-Mi; Li, Weiwei; Sun, Xing; Maity, Tuhin; Wu, Rui; Jian, Jie; Xue, Sichuang; Cho, Seungho; Wang, Haiyan; MacManus-Driscoll, Judith L.
Abstract : Combined strain + doping method is used in a VAN system to realise exemplary properties which cannot be realised in plain films. Abstract : Strongly correlated manganites have a wide range of fascinating magnetic and electronic properties, one example being the coexistence of ferromagnetic and insulating properties in lightly-doped bulk. However, it is difficult to translate bulk properties to films. Here, this problem is overcome by thin film nanoengineering of the test case system, La0.9 Ba0.1 MnO3 (LBMO). This was achieved by using vertically aligned nanocomposite (VAN) thin films of LBMO + CeO2 in which CeO2 nanocolumns form embedded in a LBMO matrix. The CeO2 columns produce uniform tensile straining of the LBMO. Also light Ce doping of intrinsic cation vacancies in the LBMO occurs. Together, these factors strongly reduced the double exchange coupling and metallicity. Hence, while standard plain reference films showed an insulator-to-metal transition at >200 K, originating from defects and complex structural relaxation, the VAN LBMO films exhibited ferromagnetic insulating properties (while maintaining a T c of 188 K). This is the first time that a combined strain + doping method is used in a VAN system to realise exemplary properties which cannot be realised in plain films. This work represents an important step in engineering high performance spintronic and multiferroic thin film devices.